Structure and flexibility: systemic and explicit assignment extensions foster an inclusive learning environment - Ruesch, Joseph M.; Sarvary, Mark A. (Frontiers in Education, 2024)
Many educators strive to create inclusive classrooms where students receive not only knowledge but also empathy from their instructors. When students face unexpected challenges due to illness, academic pressure, or exhaustion, they often seek extensions on assignments. Instructors insert their own biases when they decide who is eligible for an extension. An explicitly communicated penalty-free extension system can eliminate this bias, create an inclusive learning environment, and disinter extension requests from the hidden curriculum. Students used an "extension without penalty" system (an explicit penalty-free extension system (EWP)) in a large introductory biology course. Mid-semester qualitative data collection helped design an end-of-the-semester quantitative survey about students' perceived benefits. Assignment submission data, EWP use frequency and grades were directly extracted from the learning management system. Students preferred a two-tier extension system with ideal and extension due dates. The EWP system was used by 78% of the students, but half of them only used it once. Students reported benefits in stress reduction, handling of sickness and emergencies, and improved performance in other courses. Exploratory results indicate there were significantly greater benefits in some areas for first-generation college and PEER students. Using the extension due dates did not impact student grades. This study uses evidence to debunk common misconceptions about assignment extensions.